Positive psychological well-being and cardiovascular health - Zuccarella-Hackl, Claudia; Princip, Mary; Sivakumar, Sinthujan; von Känel, Roland (Frontiers in Psychiatry, 2024)
Positive psychological well-being (PPWB) is increasingly recognized as a critical factor in cardiovascular health of both healthy individuals and those with cardiovascular diseases (CVD). This mini-review synthesizes the current state of knowledge on the relationship between PPWB and cardiovascular health, examining relevant studies on PPWB in both populations. The conceptualization of PPWB encompasses hedonic and eudaimonic facets, with constructs such as optimism, purpose in life, and vitality playing crucial roles. Studies among healthy individuals show a significant association between PPWB and improved cardiovascular health indicators, while research among cardiac patients highlights the importance of PPWB in predicting outcomes such as mortality and rehospitalization. Mechanistic pathways linking PPWB and cardiovascular health include biological processes, health behavior changes, and additional psychological resources that mitigate stress. Despite the growing evidence, questions remain unanswered, necessitating further research to understand these relationships and develop effective interventions. Promoting psychological well-being alongside physical health can enhance cardiovascular disease prevention and management, offering a comprehensive approach to improving patient outcomes and overall well-being.